Integrating Translanguaging Informed Scaffolding and Digital Rehearsal Within Case Based Project Learning to Reduce EFL Speaking Anxiety - Ayu Melati Ningsih; Vera Kristiana; Misla Geubrina; Lisa Septia Dewi Br Ginting; Fadilla Afza Hayani (IKIP Siliwangi, 2026)
Speaking anxiety remains a major affective barrier in English as a Foreign Language (EFL) higher education. Although research since (Horwitz et al., 1986) has consistently shown a negative relationship between anxiety and performance, few studies have translated these findings into integrated instructional design. This developmental study investigates affective, linguistic, and pedagogical conditions in Indonesian undergraduate public speaking courses and proposes a Digital Case Study and Project-Based Learning (D-CS&PjBL) framework. Data were collected from 50 students and 7 lecturers using the Foreign Language Classroom Anxiety Scale (FLCAS), classroom observations, interviews, focus group discussion, and digital perception surveys. Results indicate that 42% of students experience high speaking anxiety, primarily driven by fear of negative evaluation. Code mixing emerged as cognitive affective scaffolding aligned with translanguaging theory, while asynchronous rehearsal through Flip enhanced confidence but lacked systematic integration. The porposed framework embeds translanguaging informed scaffolding and digital rehearsal within inquiry based project cycles. An effect size simulation (Cohen’s d=0.50) suggests moderate projected impact for future quasi experimental validation. The study contributes to affective second language acquisition research and multilingual digital pedagogy.